Genomic analysis of a hop-resistance Lactobacillus brevis strain responsible for food spoilage and capable of entering into the VBNC state. (August 2020) - Xu, Zhenbo; Xu, Ruirui; Soteyome, Thanapop; Deng, Yang; Chen, Ling; Liang, Yi; Bai, Caiying; Huang, Tengyi; Liu, Junyan; Harro, Janette M.; Kjellerup, Birthe V.
Abstract: Background: Lactobacillus brevis is a major contaminant of spoiled beer. And it was able to enter VBNC state and cause false negative detection, which poses a major challenge to the brewing industry. Methods: The genomic DNA of L. brevis BM-LB13908 was extracted and purified to form a sequencing library that meets the quality requirements and was sequenced. The sequencing results were then screened and assembled to obtain the entire genome sequence of L. brevis . Predicted genes were annotated by GO database, KEGG pathway database and COG functional classification system. Results: The final assembly yielded 275 scaffolds of a total length of 2 840 080 bp with a G + C content of 53.35%. There were 2357, 701, 1519 predicted genes with corresponding GO functional, COG functional, and KEGG biological pathway annotations, respectively. The genome of L. brevis BM-LB13908 contains hop resistance gene horA and multiple genes related to the formation of VBNC state. Conclusions: This report describes the draft genome sequence of L. brevis BM-LB13908, a spoilage strain isolated from finished beer sample. This study may support further study on L. brevis and other beer spoilage bacteria, and prevent and control beer spoilage caused by microorganisms. Highlights: This report describes the draft genome sequence of L. brevis BM-LB13908, a spoilage strain isolated from finished beer sample. The final assembly yielded 275 scaffolds of a total length of 2, 840, 080 bp with a G + C content of 53.35%. 2357, 701 and 1519 predicted genes with corresponding GO functional, COG functional, and KEGG pathway annotations, respectively. The genome of L. brevis BM-LB13908 contains hop resistance gene horA and multiple genes related to the VBNC state formation.